Alcaloides isoquinolínicos e atividade citotóxica in vitro de Hippeastrum canastrense J. Dutilh & R. S. Oliveira (Amaryllidaceae) - Vicente, Andressa Reis (2016)
The Amaryllidaceae family lies between the 20most applied plant families as therapeutic agents against various diseases.An important characteristic of this family is the presence of a unique group of alkaloids, exhibitingseverals biological activities such as antitumor, antibacterial, antifungal, antimalarial,antiviral, analgesic, and antiparasiticand acetylcholinesteraseinhibition. This work presents a chemical study of the alkaloidscontent found in the bulbs and flowerlystems of Hippeastrum canastrense, an endemic species from Brazilthat notably has no studies concerning it’s chemicals components so far. In addition,the investigation of the cytotoxicityeffects of the extracts and alkaloidsisolatedwere carried out with tumor cells assays. Therefore, a classical acid-base extraction of methanol extracts of both parts of H. canastrensewas performed, followed by chromatographic separation techniques in order to isolate the alkaloids present in the species.The GC-MS analysis was ableto identify 40 alkaloids, and 16 well-known alkaloidswere isolated: sanguinine(1), hippeastrine(4), candimine(5), 7-methoxy-O-methyllycorenine(7), albomaculine(8), homolycorine(9), lycorine(10), 8-O-demethylhomolycorine(13), norpluviine(14), 2a,7-dimethoxyhomolycorine(15), 2a-hydroxihomolycorine(16), 2a-hydroxialbomaculine(17), masonine(18), normasonine(19), nerinine(20), e trisphaeridine(21), and yet five novel alkaloids here reported as 8-O-demethyl-2a-hydroxihomolycorine(2), 7-methoxymasonine(3), 2-O-metthylcandimine(6), 7-methoxynormasonine(11) e 2a-methoxyhomolycorine(12).Thecrudeextracts and enriched extracts, as well as the compounds 1, 3, 4, 5, 6, 7, 8, 10, 11, 12, 13, 15, 18, 19e 20 were evaluated for their cytotoxicity in normal fibroblast-cells and also for breast, liver and panceas tumor-cells.The alkaloids hippeastrine, candimine and lycorine showedsignificantcytotoxic effect in all assays. The lowest IC50values for hippeastrine and candimine were obtained for human pancreatic carcinoma cells, while for lycorine was in hepatocelluar carcinoma cells assays.The crude extracts of Hippeastrum canastrenseshowed remarkable cytotoxicity in tumor cells especially in hepatocellular carcinoma cells. The ethyl acetate alkaloids-enriched extracts from the flowerly stems and bulbs, along with the hexane extract from bulbs expressed a relevant cytotoxic potencial in tumor cells. However, bulbs extracts appears to be most selective then the extracts of flowerly stems